A plasmid-mediated type III secretion system associated with invasiveness and diarrheagenicity of Providencia rustigianii - Jayedul Hassan; Atsushi Hinenoya; Noritoshi Hatanaka; Sharda Prasad Awasthi; Goutham Belagula Manjunath; Nahid Rahman; Jyoji Yamate; Shota Nakamura; Daisuke Motooka; Akira Nagita; Shah M. Faruque; Shinji Yamasaki (mBio)
ABSTRACT We have recently described a clinical isolate of Providencia rustigianii strain JH-1 carrying the genes for cytolethal distending toxin (CDT) in a conjugative plasmid. A cdtB mutant of strain JH-1, which lost CDT activity, was still found to retain invasiveness and diarrheagenicity. The strain was subjected to phenotypic and genetic analyses including whole genome sequencing (WGS) to explore the genetic determinants of the observed invasiveness and diarrheagenic properties. Analysis and annotation of WGS data revealed the presence of two distinct type III secretion systems (T3SS) in strain JH-1, one of which was located on the chromosome designated as cT3SS (3,992,833 bp) and the other on a mega-plasmid designated as pT3SS (168,819 bp). Comparative genomic analysis revealed that cT3SS is generally conserved in Providencia spp. but pT3SS was limited to a subset of Providencia spp., carrying cdt genes. Strain JH-1 was found to invade HeLa cells and induce fluid accumulation with characteristic pathological lesions in rabbit ileal loops. Remarkably, these phenomena were associated with the pT3SS but not cT3SS. The plasmid could be transferred by conjugation from strain JH-1 to other strains of P. rustigianii, Providencia rettgeri, and Escherichia coli with concomitant transfer of these virulence properties. This is the first report of a functional and mobile T3SS in P. rustigianii and its association with invasiveness and diarrheagenicity of this bacterium. These data suggest that P. rustigianii and other CDT-producing Providencia strains might carry T3SS and exert their diarrheagenic effect by exploiting the T3SS nano-machinery.IMPORTANCEThe precise mechanism of virulence of Providencia rustigianii is unclear, although some strains produce cytolethal distending toxin as a putative virulence factor. We have detected the presence of a type III secretion system (T3SS) for the first time on a plasmid in a P. rustigianii strain. Plasmid-mediated T3SS seems to be directly involved in virulence of P. rustigianii and may serve as a means of horizontal transfer of T3SS genes. Our results may have implication in understanding the mechanism of emergence of new pathogenic strains of P. rustigianii.